The Commemoration of the Reformation and Mid-Nineteenth-Century Evangelical Identity. Issue 1 (1st April 2014) - Wolffe, John
Abstract : This article explores evangelical perceptions of the Reformation, with particular reference to the commemoration in 1835 of the tercentenary of the publication of Coverdale's English Bible. The first half of the nineteenth century saw a growth in evangelical interest in the Reformation, although historical understanding of the sixteenth century was initially unsophisticated and simplistic equations between past and present were widespread. The 1835 commemoration exposed a tendency to use history as a tool in contemporary controversies between Anglicans and Protestants Dissenters, as well as in the polemics of both against Roman Catholics. It also, however, helped to stimulate the growth of serious scholarly inquiry and publication about the Reformation, notably in the formation (1840) of the Parker Society. The commemorations of the tercentenaries of the accession of Elizabeth I (1858) and of the Scottish Reformation (1860) provide concluding vantage points from which to view the development of historical understanding of the Reformation during the preceding quarter century.